The Effect Of Streptomycin And Clindamycin On Dnase I Activity On The Quality Of DNA Of Salivary Origin - Hamimatur Rohmah; zulham zulham (Al-Makki Publisher, 2023)
Deoxyribonucleic acid (DNA) contains genetic material with all an individual’s information. Saliva has the potential to be a good source of human DNA. When compared to blood sampling, saliva is easier to collect and the collection process is non-invasive. However, human DNA collected from saliva has the potential to be degraded due to deoxyribonuclease (DNase) activity in saliva. DNase activity can be inhibited by antibiotics, such as aminoglycoside antibiotics and lincomycin derivatives. This study aimed to determine the effect of streptomycin and clindamycin on DNAse I activity against the quality of human genomic DNA from saliva. The sampling technique was that samples were collected from 9 subjects with each subject flowing into a saliva pot. Before saliva collection, subjects were asked to rinse their mouth with a solution of chlorhexidine gargle (Listerin™) for 30 seconds, then the samples were divided into four groups. The average concentration of DNA extracted from the spin-column method was 32.91 g/mL (7.10-99.45 g/mL) while the average purity was 1.813 g/mL (1.639-2.043 g/mL). With clindamycin treatment, PCR was able to amplify the human NOTCH2 gene ( 704 bp) while various concentrations of streptomycin produced multiple bands of 100 bp. The concentration of 3.2 mM clindamycin effectively inhibits DNAse I activity and can amplify the human NOTCH2 gene while streptomycin cannot protect.